2020
DOI: 10.1038/s12276-020-0373-5
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth is associated with epigenetic programming of transgenerational hypertension in mice

Abstract: Renal and cardiovascular complications of prematurity are well established, notably the development of hypertension in adulthood. However, the underlying molecular mechanisms remain poorly understood. Our objective was to investigate the impact of prematurity on the ontogenesis of renal corticosteroid pathways, to evaluate its implication in perinatal renal complications and in the emergence of hypertension in adulthood. Swiss CD1 pregnant mice were injected with lipopolysaccharides at 18 days of gestation (E1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…There is a timely requirement for gene transcription regulation during normal development. In this case, only the genes that are specific to a particular cell type and developmental stage are transcriptionally active [84,85]. The ability to conduct gene transcriptional modulation provides "plasticity" during development [86,87].…”
Section: Epigenetic Programming and Neonatal Chronic Lung Diseasementioning
confidence: 99%
“…There is a timely requirement for gene transcription regulation during normal development. In this case, only the genes that are specific to a particular cell type and developmental stage are transcriptionally active [84,85]. The ability to conduct gene transcriptional modulation provides "plasticity" during development [86,87].…”
Section: Epigenetic Programming and Neonatal Chronic Lung Diseasementioning
confidence: 99%
“…This phenomenon is particularly interesting. It can be hypothesized that the mechanism is as follows: GA mainly influences children by the duration of the intra or extra uterine environmental exposure and affects the degree of fetal organ development through perinatal reprogramming [ 43 ]. It is determined by the maternal and/or fetal health condition.…”
Section: Discussionmentioning
confidence: 99%
“…These sex differences are not linked to a variability in HPA axis function [ 33 ], but they may be in relation with a higher sensitivity to the administration of antenatal corticosteroids in boys [ 124 ]. In a model of lipopolysaccharide-induced prematurity, generated by our group, we observed that former preterm males develop significant hypertension in adulthood [ 125 ]. This hypertension is associated with early changes in the expression of different players of the corticosteroid signaling pathway during the neonatal period.…”
Section: Consequences In Pathophysiologymentioning
confidence: 99%
“…In our mouse model, we identified a transmission of blood pressure dysregulation to subsequent generations from preterm neonates, up to the third generation. Interestingly, this vascular anomaly was only transmitted in males in the second and third generation, which is associated with a significant increase in expression of the corticosteroid target gene Gilz and a global hypomethylation of its promoter [ 125 ]. This study demonstrates that a predisposition to arterial hypertension could be epigenetically programmed in males by events occurring during the perinatal period in previous generations through sexually dimorphic adverse activation of corticosteroid signaling pathway.…”
Section: Consequences In Pathophysiologymentioning
confidence: 99%